DEPRESSION IN TYPE 2 DIABETIC PATIENTS PRESENTING TO A TERTIARY CARE HOSPITAL IN PAKISTAN - Farhan, Ahmed; Ayub, Amir Raza; zafar, Jamal (Journal of Ayub Medical College Abbottabad, 2017)
Background: Diabetes affects almost every system including mental health. When depression and diabetes coexist, the outcome is even worse. This study was conducted to find the prevalence of comorbid depression in diabetic patients and its association with diabetic control. Methods: This was a descriptive cross sectional observational study conducted in the department of general medicine of Pakistan Institute of Medical Sciences, Islamabad from March to September 2014. A total of 223 adult diabetic patients 30-60 years of age were enrolled. Becks Depression score (BDI) and HDRS (Hamilton Depression Rating Score) of each patient was calculated. Patients were stratified into various categories based on their demographics, depressions scores and diabetic control (by means of HbA1C). Percentages, frequencies and means were calculated accordingly using SPSS-16. Results: Out of a total of 223 patients, 55.6% were females while the rest (44.4%) were males. The mean age of the patients was 51 years. Majority of the patients were uneducated (35.9%). Eighty-seven% were married, Mean BMI, duration of diabetes and HbA1C were 27 Kg/m2, 8.3 years±6.1 years and 8.15±2.13% respectively. Mean BDI and HDRS were 9.97±9.42 and 6.27±6.74 respectively. 25.6% and 21.1% of the patients had at least some degree of depression when assessed by BDI and HDRS score respectively. Conclusion: Depression is common in diabetic patients especially females, uneducated, have social issues like widows, those having long standing diabetes and those who have uncontrolled blood sugars. Keywords: Depression; Diabetes; HbA1C; BDI; HDRS